1996
DOI: 10.3109/17453679608995603
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent ipsilateral fractures of the hip and femoral shaft:A meta-analysis of 659 cases

Abstract: To cite this article: Antti Alho (1996) Concurrent ipsilateral fractures of the hip and femoral shaft:A meta-analysis of 659 cases, Acta Orthopaedica Scandinavica, 67:1, 19-28,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
106
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 41 publications
6
106
1
3
Order By: Relevance
“…The results of the current study with 77% union in the femoral shaft fractures and 100% union in the femoral neck fractures confi rm the results of Alho [19,20] and Watson and Moed [10] and emphasize that both fractures should be tackled with equal degrees of seriousness, concern and care due to their drastic complications. Both must be anatomically reduced and rigidly fi xed.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of the current study with 77% union in the femoral shaft fractures and 100% union in the femoral neck fractures confi rm the results of Alho [19,20] and Watson and Moed [10] and emphasize that both fractures should be tackled with equal degrees of seriousness, concern and care due to their drastic complications. Both must be anatomically reduced and rigidly fi xed.…”
Section: Discussionsupporting
confidence: 74%
“…However, Alho [19,20] thought that femoral shaft fracture was the main determining factor in patients' overall outcome as also reported by Watson and Moed [10], who have shown that femoral shaft nonunion is more diffi cult to treat with some patients requiring more than one revision surgery to achieve union. The results of the current study with 77% union in the femoral shaft fractures and 100% union in the femoral neck fractures confi rm the results of Alho [19,20] and Watson and Moed [10] and emphasize that both fractures should be tackled with equal degrees of seriousness, concern and care due to their drastic complications.…”
Section: Discussionmentioning
confidence: 91%
“…3,6,7 In a metaanalysis of 659 such fractures, traffic accidents accounted for 78% of the cases and 13% were due to other types of trauma. 11 Most of the patients were young men and had multi-system injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, shaft femoral fractures were associated with high-energy trauma and multiple injuries, and, in these cases, CT scanning is commonly used in standard work-up [9,11]. Fluoroscopic examination of the femoral neck is needed if CT is not available, to allow the full assessment of fractures before operation [12].…”
Section: Discussionmentioning
confidence: 99%